Biomassa fibrosa do milho: propriedades e aplicações - Ribeiro, Alline Emannuele Chaves (2017)
The aim of the present study was to verify the physical, chemical and microbiological viability of the flour derived from fibrous biomass of maize (FBMF) from the processing of maize flour “biju” type as a new food ingredient; to evaluate the nutritional and technological viability of biscuits, toast and cereal bar produced with the FBMF, by means of the evaluation of its physicochemical, microbiological and sensorial characteristics; and analyze the physicalchemical, microbiological and sensory stabilities of the cereal bar selected as the best in sensory analysis. The fibrous biomass of maize (FBM), obtained in the processing of maize flour “biju” type can be recommended for use as a new ingredient in food products, because it presents no microbiological risk; and it has high nutritional and functional value, mainly because it is rich in dietary fibers, mainly insoluble, and possess high antioxidant capacity. The production of biscuits and toast from the partial replacement of wheat flour (WF) by fibrous biomass of maize flour (FBMF) is nutritionally and technologically viable, since the evaluated samples do not present microbiological risk; have good sensory acceptance; and are source of protein and rich in insoluble dietary fibers. The utilization of the FBMF in cereal bars (CBs) is feasible from technological and nutritional point of view. The formulation CB6 (14 g 100 g-1 FBMF, 8 g 100 g-1 of rice flakes and 8 g 100 g-1 of oat flakes) presented food safety and better sensory profile, and can be classified as a food rich in dietary fiber and protein source, with high nutritional and functional appeal. The temperature and time influence the physicalchemical and sensorial characteristics of the cereal bar stored at 25 and 35 °C for 180 days. Sensory parameters (appearance, color, aroma, texture, taste and overall impression) and intent to purchase of CB were more stable over time for the cereal bar stored at 25 °C. Shelf life of the cereal bar was estimated to be approximately 153 days when maintained at 25 °C, and 87 days when stored at 35 °C.